Microlaryngoscopy - Findings review - Rodrigues, Jorge (2017)
Several diseases can affect the larynx, deteriorating their functions. Indirect laryngoscopy and laryngeal nasofibroscopy are the most consensual initial assessment. Microlaryngoscopy allows a detailed observation, possibility of palpation and biopsy. This study aims to characterize laryngeal lesions that led to microlaryngoscopy.We performed a retrospective review of all microlaryngoscopies between January 1993 and December 2014.We analyzed 863 patients, 68% with benign lesions, 8% with dysplasia and 22% with malignant neoplasm. Polyps were found in 40% of cases. Squamous papilloma was observed in 2,8% of patients. Squamous cell carcinoma was the commonest malignancy, with a marked predominance in males.Polyps and nodules were the commonest benign lesions. Squamous papilloma had increasing frequency. Squamous cell carcinoma of the larynx is very common in our population.